Exclusion of a Physician’s Liability for Performing a Medical Procedure Without the Patient’s Consent - Daszkiewicz, Krystyna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
The paper is an English translation of the article “Uchylenie odpowiedzialności lekarza za wykonanie zabiegu leczniczego bez zgody pacjenta” published originally in Palestra, no. 11–12 from 2002. The text is published as a part of a section of the Adam Mickiewicz University devoted to the achievements of the Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.